Cover and Uncover Eric Cameron (Art in Profile, 2011)
Eric Cameron is a major contemporary Canadian artist. Born in 1935 in Leicester, England, he arrived in Canada in the 1970s and has taught at the University of Guelph, the Nova Scotia College of Art and Design, and at the University of Calgary. Over the years Cameron has also continued to work in his primary medium, painting, but moved from traditional figuration to a highly conceptual practice with both his process paintings and his "thick" paintings. He has also expanded into video and has written a great deal about his work. His inspired teaching and unusual art have been recognized with major awards, including the Victor Lynch-Staunton Award (1993), the Gershorn Iskowitz Prize (1994), and the Governor General's Award (2004). Despite Cameron's prominence, much of the writing about him to date, primarily essays in exhibition catalogues, is by the artist himself. Cover and Uncover thus makes a major contribution to the field as it explores in depth Eric Cameron's art and philosophy. The book is composed of four essays, each covering a different aspect of Cameron's art, starting with Peggy Gale's analysis of his writing, then turning to Ann Davis's consideration of his process paintings and his philosophy, moving to Diana Nemiroff's review of his videos, and concluding with Thierry de Duve's observations on his Thick Paintings and his blind rejection of chance. The essays, though written independently, resonate with each other so that the reader comes away with a full picture of a complex artist, his life, his thought, his art production, and how these elements inform each other and have evolved through time. The expert commentary here, richly illustrated with Cameron's works in multiple media, provides a vital and long overdue critical lens through which to view this important artist.